2016
DOI: 10.1007/s11136-016-1454-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and establishing national norms for mental wellbeing using the short Warwick–Edinburgh Mental Well-being Scale (SWEMWBS): findings from the Health Survey for England

Abstract: PurposeThe Warwick–Edinburgh Mental Well-being Scale (WEMWBS), 14 positively worded statements, is a validated instrument to measure mental wellbeing on a population level. Less is known about the population distribution of the shorter seven-item version (SWEMWBS) or its performance as an instrument to measure wellbeing.MethodsUsing the Health Survey for England 2010–2013 (n = 27,169 adults aged 16+, nationally representative of the population), age- and sex-specific norms were estimated using means and percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
319
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 369 publications
(367 citation statements)
references
References 21 publications
30
319
17
1
Order By: Relevance
“…We also asked care-givers who they were providing care for, with the most common response among the women being a member of their family of origin and the most common among the men being a friend. In contrast to studies that have found over a third of LGBT people to be looking after a partner , we found it Note: Psychological distress was measured using the K10 Psychological Distress Scale (Kessler et al, 2002), positive mental health was measured using the Short Warwick Edinburgh Mental Well-Being Scale (SWEMWBS) (Fat et al, 2017), physical health was measured using a single-item measure of self-rated general health (Idler & Benyamini, 1997) and social support was measured using the Interpersonal Support Evaluation List (ISEL) (Cohen et al, 1985). a Not adjusted for socio-demographic variables.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…We also asked care-givers who they were providing care for, with the most common response among the women being a member of their family of origin and the most common among the men being a friend. In contrast to studies that have found over a third of LGBT people to be looking after a partner , we found it Note: Psychological distress was measured using the K10 Psychological Distress Scale (Kessler et al, 2002), positive mental health was measured using the Short Warwick Edinburgh Mental Well-Being Scale (SWEMWBS) (Fat et al, 2017), physical health was measured using a single-item measure of self-rated general health (Idler & Benyamini, 1997) and social support was measured using the Interpersonal Support Evaluation List (ISEL) (Cohen et al, 1985). a Not adjusted for socio-demographic variables.…”
Section: Discussioncontrasting
confidence: 81%
“…These results suggest that there may be a negative impact of caring for someone who is LGBTI as opposed to someone who is not, and that this impact is potentially greater for lesbian women than for gay men. We know of no other studies that have distinguished Note: Psychological distress was measured using the K10 Psychological Distress Scale (Kessler et al, 2002), positive mental health was measured using the Short Warwick Edinburgh Mental Well-Being Scale (SWEMWBS) (Fat et al, 2017), physical health was measured using a single-item measure of self-rated general health (Idler & Benyamini, 1997) and social support was measured using the Interpersonal Support Evaluation List (ISEL) (Cohen et al, 1985). a Not adjusted for socio-demographic variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…a n = 50. b n = 49. of frailty with a lower grip strength and slower gait speed than population averages 244,245 and had an average of three or four long-term health conditions. Mental well-being scores were slightly lower than age-adjusted population norms of 51.6 points 246 and levels of psychological distress were high, with the mean GHQ-12 score at baseline (13.4) being higher than the accepted threshold for a 'case' of psychological distress of 11/12.…”
Section: Feasibility Randomised Controlled Trial: Resultsmentioning
confidence: 68%
“…it is negatively associated with good overall well-being (Fat, Scholes, Boniface, Mindell, & Stewart-Brown, 2017) and positively with depression (Ludin, Hallgren, Theobald, Hellgren, & Torgen, 2016).…”
Section: Demographic Surveymentioning
confidence: 99%